Phytochemical and Antioxidant Activity Tests of Ethanol Extracts of the Roots, Stems and Leaves of Song of India (Dracaena reflexa) Plant Using the DPPH Method - Faleria Sandra Puspita; Agung Tri Prasetya (Universitas Negeri Semarang, 2023)
An antioxidant is a substance needed by the body with its function to neutralize damage to the body caused by radicals, which cause a degenerative disease in normal cells. The body naturally produces an antioxidant, but its use in protecting against free radicals is unknown. One of the other efforts to prevent it is by obtaining antioxidants from outside the body which can be found through natural ingredients such as Dracaena reflexa. The Dracaena reflexa plant is a plant that has been widely spread, especially in the city of Semarang. This plant is a traditional medicinal plant that is trusted and used as a treatment by the State of Madagascar. However, this plant has not been widely explored for its biological potential in 70% ethanol solvent. This research was carried out by determining bioactive compounds through phytochemical tests as an initial step method. Then, the total phenolic content and total flavonoid content were determined, compound analysis using GC-MS and IC50 determination of antioxidant activity using DPPH. High levels of total phenol obtained in roots, stems and leaves between 111.44 ± 2.4056 - 67.556 ± 2.0972 mgGAE/g. Meanwhile, high levels of flavonoids in roots, stems and leaves were between 43.555 ± 6.938 - 30.222 ± 3.849 mgQE/g in stems. Thus, the IC50 gain for each part resulted in different criteria, namely leaves with moderate antioxidant criteria, stems with very weak antioxidant criteria and roots with weak antioxidant criteria. Furthermore, the main compounds identified in the analysis using GC-MS identified the presence of 3 groups of dominant compounds obtained, namely fatty acids, terpenoids and ethanol. The results of the study indicate that Dracaena reflexa needs to be further explored for its use in curing various diseases.